SUSTAINABILITY AND DECISION MAKING COAL TRANSPORTATION AT COAL MINING PIT C2 SAMBARATA MINING OPERATION PT. BERAU COAL - Saputro, Arintoko
PT. Berau Coal is a coal mining company in Berau Regency, East Kalimantan, where one of the operating sites is the Sambarata Mine Operation with the C2 Pit mining area. One of the biggest challenges in the Pit C2 coal mining process is the transportation of coal from the pit/mine to the coal processing plant (CPP) with an average distance of 10 Km. The background of this project is that there has been an increase in fuel consumption in coal transportation by an average of 51% per month in the period July - December 2021. Fuel contributes around 40% of coal mining operational costs in Pit C2, so this is a burden for increased costs from the company. The cause of this increase is the change in the coal mining method to double handling where the use of HD 773 units (Haul Dump series 773) from Pit to temporary ROM, then from temporary ROM using DT 30 tons to CPP. Under these conditions, it is necessary to choose the right coal transportation equipment, so that mining operations can be effective, efficient and productive, especially in terms of fuel consumption. The author uses the Simple Multi Attribute Rating Technique ( SMART ) and Analytical Hierarchy Process ( AHP ) methods. Where in AHP it is specifically divided into 3 criteria and 6 sub criteria. These criteria are Cost, Safety, and Infrastructure and the 6 sub criteria used are fuel consumption, productivity, vessel capacity, haul roads, weighbridges and crushing equipment. Alternative solutions are presented at the improvement stage with reference to the coal mining business process, namely through selecting the use of dump truck units with a capacity of 30 tons, 45 tons, 60 tons and 70 tons. From the results of the AHP analysis, it is found that optimal coal transportation from Pit C2 to CPP in the Sambarata Mine Operation area is the use of a Loadpro unit with a capacity of 60 tons. Using a 60 ton DT unit will have the impact of reducing the coal mining fuel ratio to 18.91% / month ($ 25,290 / month).